Clarifying Recent Adaptive Diversification of the Chrysanthemum-Group on the Basis of an Updated Multilocus Phylogeny of Subtribe Artemisiinae (Asteraceae: Anthemideae) - Shen, Chu-Ze; Zhang, Chu-Jie; Chen, Jie; Guo, Yan-Ping (Frontiers in Plant Science, 2021)
Understanding the roles played by geography and ecology in driving species diversification and in the maintenance of species cohesion is the central objective of evolutionary and ecological studies. The multi-phased orogenesis of Qinghai-Tibetan Plateau (QTP) and global climate changes over late-Miocene has profoundly influenced the environments and evolution of organisms in this region and the vast areas of Asia. In this study, we investigate the lineage diversification of Chrysanthemum-group in subtribe Artemisiinae (tribe Anthemideae, Asteraceae) likely under the effects of climate changes during this period. Using DNA sequences of seven low-copy nuclear loci and nrITS and the coalescent analytical methods, a time-calibrated phylogeny of subtribe Artemisiinae was reconstructed with emphasis on Chrysanthemum-group. The monophyletic Chrysanthemum-group was well resolved into two major clades corresponding to Chrysanthemum and Ajania, two genera which can be well identified by capitulum morphology but have been intermingled in previous plastid and ITS trees. Within Chrysanthemum, a later divergence between Ch. indicum-complex and Ch. zawadskii-complex can be recognized. The time frames of these sequential divergences coincide with the late Cenozoic uplift of the Northern QTP and the concomitant climatic heterogeneity between eastern and inland Asia. Reconstruction of historical biogeography suggested the origin of Chrysanthemum-group in Central Asia, followed by eastward migration of Chrysanthemum and in situ diversification of Ajania. Within Chrysanthemum, Ch. indicum-complex and Ch. zawadskii-complex exhibited contemporary distributional division, the former in more southern and the latter in more northern regions. The geographic structure of the three lineages in Chrysanthemum-group have been associated with the niche differentiation, and environmental heterogenization in Asia interior.